Effective social media features as strategy platform teaching and learning during the Movement Control Order (MCO) period - Lee, Lilian Shiau Gee; Victor Pangayan; Chia, Yee Ee; Jasni Dolah (Turkish Physiotherapy Association, 2021)
This paper presents the results of a study to identify the adoption of collaborative study by university students, especially by using technology as an alternative option in the COVID-19 pandemic. This study outlines the user interface that learners plan to pursue and the factors affecting the selection of applications. The study consisted of 202 students from universities. Data were collected via an online questionnaire of Google Forms. Empirical data analysis shows that social media approaches need the characteristics of successful information exchange, interactive social media functionality, and constructive usability to improve students' motivational attitudes towards perceived usability and user - friendliness. The paper also addresses the characteristics of the e-learning approach by using apps as well as measures to improve the efficiency of visualizing applications appropriate for local students to optimize learning outcomes. The finding provides insights into the necessity of social media features that are advantageous for scholars and practitioners interested in developing social media learning applications.